Modeling and simulation of oxidative coupling of methane in a heat-exchange integrated microchannel reactor - Tezcan, Funda İdil. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2013., 2013)
Oxidative coupling of methane (OCM) involves catalytic conversion of methane into C2 hydrocarbons (ethane and ethylene) and offers an alternative oil-free production of important feedstock used in petrochemical industry. OCM requires effective temperature control since the product distribution depends strongly on temperature. Integration of OCM with microchannel reactor technology can lead to a novel process, since the micro-technology has advantages like significant intensification of the process which minimizes the transport resistances and allows robust temperature control. The aim of this study is to investigate OCM in a cooling flow enabled heat-exchange integrated microchannel reactor by computer-based modeling and simulation techniques, and to demonstrate the effects of different operational and structural parameters on the reaction performance by means of temperature profile and C2 hydrocarbon yield. Steady-state simulations conducted using computational fluid dynamics (CFD) show that effective heat transfer and improved temperature distributions can be obtained in the microchannel reactor. The results indicate that, using walls with high thermal conductivity regulates temperature profile and improves the C2 hydrocarbon yield at the same time. Using thicker walls increases the average reaction temperature, but decreases the C2 hydrocarbon yield. It is observed that increasing the molar methane-to-oxygen ratio in the feed decreases the reaction temperature and conversion immediately due to reduced release of exothermal heat, resulting in lower C2 hydrocarbon yield. In contrast with the cooling channel inlet temperature, reaction channel inlet temperature has much lower effect on temperature profile. It is also observed that increasing the mass flow rate of cooling channel decreases the reaction temperature and increases the C2 hydrocarbon yield, whereas increasing the mass flow rate of the reaction channel has the opposite effect on the reaction temperature profile, leading to the oxidation of C2 hydrocarbons. The possibility of obtaining 46.8% methane conversion and 23.9% C2 yield is demonstrated.
Keywords: Methane -- Oxidation.; Methane.; Oxidation.